Updated Meta-Analysis of Randomized Trials Comparing Safety and Efficacy of Intraoperative Defibrillation Testing with No Defibrillation Testing On Implantable Cardioverter-Defibrillator Implantation - Bonanno, Carlo; Rossillo, Antonio; Paccanaro, Mariemma; Ramondo, Angelo; Raviele, Antonio (International Journal of Cardiovascular Practice, 2017)
Introduction: There is an ongoing debate regarding the need to conduct intraoperative defibrillation testing (DFT) at the time of implantable cardioverter-defibrillator (ICD) implantation. To provide sufficiently strong evidence for the feasibility of omitting intraoperative DFT in clinical practice, we conducted a meta-analysis of randomized controlled trials (RCT) comparing patients with DFT and no-DFT.Methods: We systematically searched Medline (via PubMed), ClinicalTrial.gov, the Cochrane Central Register of Controlled Trials, and Embase for studies evaluating DFT vs. no-DFT on ICD implantation with regard to total mortality and arrhythmic death, efficacy of first and any appropriate shock in interrupting ventricular tachycardia (VT)/ventricular fibrillation (VF), and procedural adverse events. Effect estimates [risk ratio (RR) with 95% confidence intervals (CI)] were pooled using the random-effects model.Results: Our meta-analysis included 4 RCTs comprising 3770 patients (1896 with DFT and 1874 without DFT). Total mortality (RR = 1.00, 95% CI 0.86â1.17; P = 0.98) and arrhythmic death (RR = 1.60, 95% CI 0.46-5.59: P = 0.46) were not statistically different. Both first (RR = 0.94, 95% CI 0.89â0.98; P = 0.004) and any appropriate ICD shock (RR = 0.97, 95% CI 0.95â1.00; P = 0.02) significantly increased the rate of VT/VF interruption in the group with no-DFT in comparison with DFT. Finally, the incidence of adverse events was lower in no-DFT patients (RR = 1.23; 95% CI 1.00â1.51; P = 0.05).Conclusions: The practice of DFT (as opposed to no-DFT) did not yield benefits in mortality or the overall rate of conversion of VT/VT. Moreover, a slightly higher incidence of perioperative adverse events was observed in the DFT group.